A Novel Self‐Amplifying mRNA with Decreased Cytotoxicity and Enhanced Protein Expression by Macrodomain Mutations - Yue Gong; Danni Yong; Gensheng Liu; Jiang Xu; Jun Ding; William Jia (Advanced Science)
Abstract The efficacy and safety of self‐amplifying mRNA (saRNA) have been demonstrated in COVID‐19 vaccine applications. Unlike conventional non‐replicating mRNA (nrmRNA), saRNA offers a key advantage: its self‐replication mechanism fosters efficient expression of the encoded protein, leading to substantial dose savings during administration. Consequently, there is a growing interest in further optimizing the expression efficiency of saRNA. In this study, in vitro adaptive passaging of saRNA is conducted under exogenous interferon pressure, which revealed several mutations in the nonstructural protein (NSP). Notably, two stable mutations, Q48P and I113F, situated in the NSP3 macrodomain (MD), attenuated its mono adenosine diphosphate ribose (MAR) hydrolysis activity and exhibited decreased replication but increased payload expression compared to wild‐type saRNA (wt saRNA). Transcriptome sequencing analysis unveils diminished activation of the double‐stranded RNA (dsRNA) sensor and, consequently, a significantly reduced innate immune response compared to wt saRNA. Furthermore, the mutant saRNA demonstrated less translation inhibition and cell apoptosis than wt saRNA, culminating in higher protein expression both in vitro and in vivo. These findings underscore the potential of reducing saRNA replication‐dependent dsRNA‐induced innate immune responses through genetic modification as a valuable strategy for optimizing saRNA, enhancing payload translation efficiency, and mitigating saRNA cytotoxicity.